2012
DOI: 10.1002/adma.201104712
|View full text |Cite
|
Sign up to set email alerts
|

Sliding on a Nanotube: Interplay of Friction, Deformations and Structure

Abstract: The frictional properties of individual carbon nanotubes (CNTs) are studied by sliding an atomic force microscopy tip across and along its principle axis. This direction-dependent frictional behavior is found to correlate strongly with the presence of structural defects, surface chemistry, and CNT chirality. This study shows that it is experimentally possible to tune the frictional/adhesion properties of a CNT by controlling the CNT structure and surface chemistry, as well as use friction force to predict its … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…In a previous study it was shown that even for very different types of nanotubes the friction anisotropy as a function of α was approximately always following the same analytical curve [12]. Thus, here we will be able to calculate α for each BN-NT with a given friction anisotropy.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In a previous study it was shown that even for very different types of nanotubes the friction anisotropy as a function of α was approximately always following the same analytical curve [12]. Thus, here we will be able to calculate α for each BN-NT with a given friction anisotropy.…”
Section: Resultsmentioning
confidence: 68%
“…Next, we fit the friction data obtained for different BN-NTs with equation (1) The measured maximum and minimum friction anisotropy (a), average transverse and longitudinal shear strengths (σT , σL (GPa)), coupling parameter (α), intrinsic shear strength (σ int (GPa)) and "hindered rolling" shear strengths (σ HR (GPa)) of BN-NTs as well as the C-NTs from Ref. [12]. than σ L , which varies between 0.02 ± 0.001 and 0.1 ± 0.01 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…To relate the contact area to the normal van der Waals adhesion force (Fn), and the static friction force (Fs) of CNT-CNT contact (Equations 6 and 7), we must know the contact strength. Previous studies employed molecular dynamics simulations and atomic force microscopy experiments to determine that CNT-CNT contact in shear can be represented by a single asperity microscale friction law 28,29 Here, A is the Hamaker's constant, d is the separation between the outer walls of the CNTs, w and Lc are the contact width and length respectively.…”
Section: Cnt-cnt Contact Length and Strengthmentioning
confidence: 99%
“…Therefore, in nominal simulations we use τ = 0.24 GPa as the interfacial shear strength for relative sliding between CVD grown CNTs. 29 In general, the interfacial shear strength depends on factors such as CNT roughness, chirality, presence of other chemical groups and defect density.…”
Section: Cnt-cnt Contact Length and Strengthmentioning
confidence: 99%
“…It is found that ds RNA are softer compared to ds DNA with similar contour length due to the existence of nicks along the RNA chain. AFM, in particular, is a powerful technique to study the elasticity of nano-systems [44][45][46][47][48], and ds DNA shorter than hundred nanometers have been investigated using AFM [49][50][51][52][53]. Remarkably, these short ds DNAs have been recently found to be much softer than few kilo base pair DNAs by means of AFM [50,52], X-ray diffraction [54,55], and fluorescence resonance energy transfer (FRET) [55] techniques.…”
Section: Introductionmentioning
confidence: 98%